Extracellular vesicle‐mediated delivery of circDYM alleviates CUS‐induced depressive‐like behaviours. Issue 1 (13th January 2022) - Yu, Xiaoyu; Bai, Ying; Han, Bing; Ju, Minzi; Tang, Tianci; Shen, Ling; Li, Mingyue; Yang, Li; Zhang, Zhao; Hu, Guoku; Chao, Jie; Zhang, Yuan; et al.
Abstract: Major depressive disorder (MDD) is the most prevalent psychiatric disorder worldwide and severely limits psychosocial function and quality of life, but no effective medication is currently available. Circular RNAs (circRNAs) have been revealed to participate in the MDD pathological process. Targeted delivery of circRNAs without blood‐brain barrier (BBB) restriction for remission of MDD represents a promising approach for antidepressant therapy. In this study, RVG‐circDYM‐extracellular vesicles (RVG‐circDYM‐EVs) were engineered to target and preferentially transfer circDYM to the brain, and the effect on the pathological process in a chronic unpredictable stress (CUS) mouse model of depression was investigated. The results showed that RVG‐circDYM‐EVs were successfully purified by ultracentrifugation from overexpressed circDYM HEK 293T cells, and the characterization of RVG‐circDYM‐EVs was successfully demonstrated in terms of size, morphology and specific markers. Beyond demonstrating proof‐of‐concept for an RNA drug delivery technology, we observed that systemic administration of RVG‐circDYM‐EVs efficiently delivered circDYM to the brain, and alleviated CUS‐induced depressive‐like behaviours, and we discovered that RVG‐circDYM‐EVs notably inhibited microglial activation, BBB leakiness and peripheral immune cells infiltration, and attenuated astrocyte disfunction induced by CUS. CircDYM can bind mechanistically to the transcription factor TAF1 (TATA‐box binding protein associated factor 1), resulting in the decreased expression of its downstream target genes with consequently suppressed neuroinflammation. Taken together, our findings suggest that extracellular vesicle‐mediated delivery of circDYM is effective for MDD treatment and promising for clinical applications.